2016
DOI: 10.1088/0964-1726/25/8/085009
|View full text |Cite
|
Sign up to set email alerts
|

Design and control of a prosthetic leg for above-knee amputees operated in semi-active and active modes

Abstract: This paper proposes a new prosthesis operated in two different modes; the semi-active and active modes. The semi-active mode is achieved from a flow mode magneto-rheological (MR) damper, while the active mode is obtained from an electronically commutated (EC) motor. The knee joint part of the above knee prosthesis is equipped with the MR damper and EC motor. The MR damper generates reaction force by controlling the field-dependent yield stress of the MR fluid, while the EC motor actively controls the knee join… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 16 publications
0
59
0
Order By: Relevance
“…The angle control approach is inherently not suitable for prostheses due to biomechanical reasons, as reported by Sup et al [ 37 ]. On the other hand, the torque control or tracking with state impedance control schemes, have already established its suitability in active prostheses [ 42 ], but its application in semi-active prostheses [ 43 ] may not be cautious enough as semi-active prostheses reported in [ 24 , 25 , 26 ] using an MR damper do not contribute to net propulsive power during walking. Its function still remains as a passive device with impedance or damping modulation despite torque control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The angle control approach is inherently not suitable for prostheses due to biomechanical reasons, as reported by Sup et al [ 37 ]. On the other hand, the torque control or tracking with state impedance control schemes, have already established its suitability in active prostheses [ 42 ], but its application in semi-active prostheses [ 43 ] may not be cautious enough as semi-active prostheses reported in [ 24 , 25 , 26 ] using an MR damper do not contribute to net propulsive power during walking. Its function still remains as a passive device with impedance or damping modulation despite torque control.…”
Section: Discussionmentioning
confidence: 99%
“…The authors used an MR knee prosthesis to adapt knee damping using local sensing of knee force, torque, and position. A few recent studies conducted by Xu et al [ 24 ], Park et al [ 25 ], and Fu et al [ 26 ] have also attempted to design a lower limb prosthesis based on an MR damper. Complex sensing, data-driven AI control and lack of local climatic adaptations as well as increased cost of the prosthesis arising from various factors ranging from non-inclusion of off-the-shelf components or locally manufactured components increased the inherent cost, making it unsuitable for applications in low-income economies.…”
Section: Prosthesis Designmentioning
confidence: 99%
“…It was reported that by controlling the damping force of MR damper, the desired knee joint angle can be accurately achieved. Park et al [85] designed and manufactured a prosthetic leg for above-knee amputees using MR damper and control performance was evaluated experimentally. The proposed device includes the wearable connector, encoder, flat motor, planetary gear head, gyro sensor, hinge, and MR damper.…”
Section: Medical and Rehabilitation Applicationsmentioning
confidence: 99%
“…In the recently decades, there are several researches about the MR damper based above-knee prosthesis (MRAKP) in the world [3][4][5][6]. Hugh Herr and Ari Wilkenfeld proposed an intelligent prosthetic knee with a MR damper and the adaptive controlling base on the finite-state machine (FSM) for the prosthetic knee [7].…”
Section: Introductionmentioning
confidence: 99%